Pengaruh Model Pembelajaran Kooperatif Tipe CRH Berbantuan Media Powerpoint terhadap Kompetensi Pengetahuan IPS Siswa - Candelia, Ni Kadek Cindy; Anak agung Gede Agung; I Gusti Agung Ayu Wulandari (Universitas Pendidikan Ganesha, 2022)
The need for appropriate learning models and media applications in social studies impacts students' low knowledge competence. This study aims to determine the significant effect of the course review horay (CRH) cooperative learning model assisted by PowerPoint media on the social studies knowledge competence of fifth-grade elementary school students. This research is a quasi-experimental study with the Nonequivalent Pre-test and Post-test Control Group Design. The population in this study was 116 students of class V SD. Sampling was carried out using cluster random sampling technique, and the number of samples in this study was 22 students of class V SD. IPS knowledge competency data was collected using the test method, with a research instrument in the form of 30 multiple choice test questions. The data obtained in the study were then analyzed using descriptive statistical analysis techniques and inferential statistical analysis. The results of the data analysis showed that the course review horay (CRH) type cooperative learning model assisted by PowerPoint media had a significant effect on the social studies knowledge competence of fifth-grade elementary school students. It was concluded that the cooperative learning model of the course review horay (CRH) type assisted by PowerPoint media could improve the competence of Social Sciences knowledge of fifth-grade elementary school students.